PENGAWETAN KAYU SENGON MELALUI RENDAMAN DINGIN MENGGUNAKAN BAHAN PENGAWET ENBOR SP DITINJAU TERHADAP SIFAT MEKANIK - Endah Kanti Pangestuti; Lashari Lashari; Agus Hardomo (Jurnal Teknik Sipil dan Perencanaan)
The use of wood in construction world continues to increase both for the use of structural and non-structural. Needs a very large timber impact on the availability of wood shrinks every year as a result of exploitation by large scale. One attempt to extend the service life of wood is the wood preservation. This study aims to determine mechanical properties of wood by soaking sengon due to cold preservation with preservative EnborSP. The method used is the method of experiments carried out in the Laboratory of Materials of Civil Engineering, Faculty of Engineering, State University of Semarang. The preservation process used isa process with a cold soaking method, with a preservative solution EnborSP with a concentration of 0%, 3%, 6% and 9%. The response observed was the value-the value retention of preservatives, and mechanical properties (compressive strength of parallel fiber direction, flexural strength and surface hardness) of wood. Preservation method applied is cold soaking (for 5 days or 120 hours). Average retention value-average increase of 2.57kg/m3 (3%), 4.89kg/m3 (6%), and 6.74kg/m3 (9%). Value - average compressive strength of parallel to the direction of the wood fiber sengon increase of 149.39kg/cm2 (0%), 156.35kg/cm2 (3%), 187.80kg/cm2 (6%), and 216, 44kg/cm2 (9%). Value average flexural strength sengon increase of 175.36kg/cm2 (0%), 202.55kg/cm2 (3%), 272.64kg/cm2 (6%), and 362.81kg/cm2 (9%). Value average penetration sengon wood decreased from 0.93cm (0%), 0.67cm (3%), 0.57cm (6%), and 0.43cm (9%). This decrease shows that there is an increase in the value of the wood sengon surface hardness.